An experimental method for effusivity determination of different scratched temperature sensors - Mohammed H.; Salleh H.; Yusoff M.Z. (2023)
This paper presents an experimental method for evaluating the effusivity values of different scratched temperature sensors. These sensors have a response time on the order of microseconds (50 ?s) with a rise time less than (0.3 ?s). Two types of scratch were used, mainly abrasive papers with different grit sizes and scalpel blades with different thicknesses to form the sensor junction. The effect of scratch technique on the sensor's effusivity is also investigated. The sensors were tested and calibrated in the test section of a shock tube facility at different operating conditions. It was observed that the effusivity of a particular sensor depends on the Mach number, scratch technique, junction location as well as on the enthalpy condition. It was also noticed that sensor scratched using scalpel blade technique does not require an individual calibration. However, for sensor scratched using abrasive paper technique, a calibration for each sensor is likely to be required. The present results have provided useful and practical data of the effusivity values for different scratched temperature sensors. These data are beneficial to the experimentalists in the field and it can be used for accurate transient heat transfer rate measurements. 2009 IEEE.